2020
DOI: 10.1177/0194599820955175
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Post–acute care Following Free Flap Reconstruction of the Oral Cavity

Abstract: Objective Identify previously unreported factors that predict the need for post–acute care after free flap reconstruction of the oral cavity. Study Design Retrospective cohort study. Setting Single academic medical center. Methods A total of 134 patients with head and neck disease involving the oral cavity underwent free tissue transfer for reconstruction between August 2012 and October 2015. All patients had a tracheostomy placed at the time of surgery. Data were collected, including demographics, perioperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 19 publications
(54 reference statements)
2
10
0
Order By: Relevance
“…This is consistent with prior head and neck literature demonstrating older patients were more likely to be discharged to a facility 15–17,20,23 . In addition to increasing age, Lepse et al found tracheostomy tube, length of hospitalization of greater than 10 days, absence of family support and government insurance to be independent risk factors for post‐acute care admissions following oral cavity free flap reconstruction 24 …”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…This is consistent with prior head and neck literature demonstrating older patients were more likely to be discharged to a facility 15–17,20,23 . In addition to increasing age, Lepse et al found tracheostomy tube, length of hospitalization of greater than 10 days, absence of family support and government insurance to be independent risk factors for post‐acute care admissions following oral cavity free flap reconstruction 24 …”
Section: Discussionsupporting
confidence: 85%
“…[15][16][17]20,23 In addition to increasing age, Lepse et al found tracheostomy tube, length of hospitalization of greater than 10 days, absence of family support and government insurance to be independent risk factors for post-acute care admissions following oral cavity free flap reconstruction. 24 In our study, in addition to advanced age, we found postoperative medical complications correlated with an increased likelihood of requiring admission to a skilled nursing or rehabilitation facility. This is to be expected, as we have previously shown the occurrence of postoperative medical complications following reconstruction with a free flap correlated with patient age.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations